The Murder At the Vicarage - Christie, Agatha (London HarperCollins Publishers, 2006)
Agatha Christie's first ever Miss Marple mystery, reissued with a striking new cover designed to appeal to the latest generation of Agatha Christie fans and book lovers.
Originally published in Great Britain: Collins, 1930.
Keywords: Marple, Jane (Fictitious character); Women detectives